Absolute configuration of a [1]rotaxane determined from vibrational and electronic circular dichroism spectra. Issue 11 (29th September 2021) - Puente, Andrew R.; Bessaguet, Adrien; Pairault, Noël; Pieters, Grégory; Crassous, Jeanne; Polavarapu, Prasad L.; Opalinski, Isabelle; Papot, Sébastien
Abstract: The experimental vibrational circular dichroism (VCD) and electronic circular dichroism (ECD) spectra were measured for the enantiomers of [1]rotaxane 1 . These experimental spectra have been analyzed using predicted VCD and ECD spectra for ( S, R mp ) or ( S, S mp ) diastereomers using density functional theory. This comparison allowed for a definitive assignment of the absolute configuration of 1 . Abstract : This article reports the absolute configuration of an enantiopure [1]rotaxane determination by comparing experimental versus theoretical ECD and VCD spectra.